Pengaruh Kompetensi Pedagogik Guru dan Keaktifan Siswa Terhadap Hasil Belajar Siswa Setingkat Menengah Pertama - Didit Darmawan; Mohammad Iqbal Fikri Adi; Achmad Afad El Barkah (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to explore and elucidate the relationship between these two factors and learning outcomes through a synthesis of relevant prior research findings. The method employed is a literature review using a qualitative approach, conducted through a critical analysis of a number of national scientific publications discussing the relationship between teachers pedagogical competencies, student engagement, and learning outcomes. The results of the study indicate that teachers’ pedagogical competencies, both in internal and external aspects, tend to have a positive and significant relationship with improved learning outcomes. Teachers with adequate pedagogical capacity are generally able to build a learning ecosystem that fosters students perseverance, focus, and resilience in facing academic challenges. On the other hand, student engagement also demonstrates a positive contribution to learning outcomes, as it reflects cognitive, affective, and psychomotor involvement in the learning process. Furthermore, the roles of teachers, the school environment, and family support were also identified as contextual factors that reinforce the dynamics of student learning engagement. Thus, strengthening teachers pedagogical competencies and optimizing student engagement can be viewed as strategic priorities in efforts to improve the quality of learning outcomes in junior high schools.